KEMAMPUAN MENGARANG DESKRIPSI BERDASARKAN OBSERVASI PADA SISWA KELAS V SDN 1 GULAK GALIK BANDAR LAMPUNG - Frieska Maryova Rachmasisca (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The problem discussed in this study was the ability to write descriptions of the Odd Semester Class of SD Negeri 1 Gulak Galik in Bandar Lampung. The research method used is descriptive qualitative method. The research sample of 30 students was taken using a stratified proportional random sampling technique from the existing population. The data collection technique was carried out by means of a performance test, which assigned students a description of the object in the school environment. Data analysis used quantitative analysis using a simple percentage formula. The results showed that the ability to write descriptions of class V Odd Semester SD Negeri 1 Gulak galik Bandar Lampung with a sufficient category with a score of 67. Of the 5 aspects that were assessed there was 1 aspect of content suitability with a score of 87.5 declared very good, 3 aspects were sufficient, namely aspects of spelling writing, written form and sentence effectiveness, and 1 aspect which is stated to be lacking in the aspect of word choice.